UJI KETAHANAN ENAM GALUR TANAMAN TOMAT (Lycopersicum esculentum Mill.) TERHADAP BEGOMOVIRUS - Ahmad Chabibul Azis; Sumarji '; Agusdin Dharma F (Jurnal Ilmiah Hijau Cendekia, 2017)
Begomovirus is one of the causes of low production of tomato in Indonesia. Begomovirus is a genus of Geminiviridae family that transmitted by Bemisia tabaci. One of to control Begomovirus which safe and profitable is use resistant of varieties. The purpose of this research is to know the level of resistance of six line tomato (Lycopersicum esculentum Mill.) inBegomovirus. This research was doing in PT. BISI International Tbk., Sumberagung Village District Plosoklaten Kediri with height place ± 220 above the sea. The study was doing from December 2016 to March 2017. The study used a random group design with six treatments, each treatment was repeated in three times. The results showed that Begomovirus’s infection take effect the growth of tomato after the plants were more than 18 days after planting. There is a difference of resistance level six line of tomato (Lycopersicum esculentum Mill.) to Begomovirus. Intensity of symptoms of Begomovirus take effect to average number production of fruit.